Post-IPO Operating Performance of Venture and Non Venture-Backed Companies in Malaysia - Sekar Suci, Asdityani (2012)
This study examines the changes in post-operating performance of venture-backed and non-venture IPO companies. Moreover,this study also expects to investigate the effect of venture capitalist and pre-IPO characteristics on post-IPO operating performance. The tests are conducted on a sample of 112 companies going public during 2002 to 2008 on MESDAQ market of Bursa Malaysia. Out of 112 IPOs,22 were venture-backed and 90 were non-venture backed IPO companies.A significant decline in operating performance subsequent to the initial public offering (IPO) is found. The evidence shows declining pcrforrnance in the IPO year and up to three years following lPOs relative to the pre-IPO period. In contrast with the previous studies,the result reports that venture-backed IPO do not generate superior post-IPO performance to non-venture backed lPOs in Malaysia evidence. Additionally, there is a significant positive relation between post-IPO operating performance and changes in VC ownership, initial return. company age and company size and also significant negative relation between pot;t-IPO operating performances with market capitalization. However no relation between post-IPO operating performance with VC dummy and company size of offering.